2020
DOI: 10.1002/ejlt.202000115
|View full text |Cite
|
Sign up to set email alerts
|

Novozyme 435 and Lipozyme RM IM Preferably Esterify Polyunsaturated Fatty Acids at the sn‐2 Position

Abstract: This work aims at studying the impact that the degree of unsaturation of fatty acids (FA) with the same chain length exerts on the esterification yield and the regiodistribution of FA in the glycerol backbone. To that end, triacylglycerols (TAG) are produced by esterifying several mixtures (stearic, oleic, and alpha-linolenic acids) employing Novozyme 435 and Lipozyme RM IM. All esterifications achieve a high content of TAG (>69 mol%) with Lipozyme RM IM being more active. Both lipases initially esterify stear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, Novozym 435 exhibited preference for short chain fatty acids and long chain fatty acids, as reported by Wu et al [62]. Duan et al [63], Misbah et al [64] and Rivero-Pino et al [65] found that many lipases had substrate specificity toward triacylglycerols with short or medium carbon chain during the hydrolysis of triacylglycerols. While for the hydrolysis of fatty acid esters, lipases expressed different selectivity.…”
Section: Substrate Specificity Of Lipasesupporting
confidence: 60%
“…However, Novozym 435 exhibited preference for short chain fatty acids and long chain fatty acids, as reported by Wu et al [62]. Duan et al [63], Misbah et al [64] and Rivero-Pino et al [65] found that many lipases had substrate specificity toward triacylglycerols with short or medium carbon chain during the hydrolysis of triacylglycerols. While for the hydrolysis of fatty acid esters, lipases expressed different selectivity.…”
Section: Substrate Specificity Of Lipasesupporting
confidence: 60%
“…In turn, for grapeseed oil, palmitic acid (16:0) was the predominant FA released [ 66 ]. Likewise, when the lipase from R. miehei was used to produce TAG enriched with PUFA throughout an esterification reaction, Rivero-Pino et al [ 78 ] reported that this enzyme initially esterifies stearic acid (18:0), while linolenic acid (18:3 n-3) is preferably esterified in the last step of the esterification, suggesting that it has a slight selectivity toward unsaturated FA.…”
Section: Resultsmentioning
confidence: 99%
“…Rivero‐Pino et al. (2020) studied the impact of several mixtures (stearic, oleic, and alpha‐linolenic acids) on the TAG production by esterifying with Novozym 435 and Lipozyme RM IM. The results showed that Lipozyme IM RM partially preferred to esterify unsaturated FA while N435 showed a random behavior in a solvent‐free system.…”
Section: Resultsmentioning
confidence: 99%